The Effect of Power Medicine Ball Training on Long Throw-In Ability in Football Athletes - Rival Vieri; Mulyana; Yudi Nurcahya (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2025)
This study aims to determine the effect of power training using a medicine ball on improving long throw-in ability in football athletes. The research method used was an experiment with a one-group pretest–posttest design, involving 12 active male football athletes in the UPI Football Student Activity Unit aged 18–20 years who play the positions of fullback and winger. The training program was carried out for 16 sessions using the set system method, including the Overhead Medicine Ball Throw, Chest Pass to Wall, Rotational Throw, and Medicine Ball Slams movements with a load of 4–5 kg and explosive intensity. The instrument used was the Throw-in Distance Measurement Test to measure the throwing distance. The Pretest score had an average (mean) of 17.11 with a standard deviation of 2.85, while the Posttest score had an average of 19.01 with a standard deviation of 3.10. The results showed a significant increase in long throw-in ability after being given training using a medicine ball. This increase occurred because the training was able to develop functional arm, shoulder, and core muscle strength through explosive movements that resemble real throwing techniques. It can be concluded that power training using a medicine ball is an effective and applicable method to improve long throw-in ability in football athletes.